Management of Research Collaboration in the Era Merdeka Belajar Kampus Merdeka (MBKM) - Abdullah, Jihan; Nurdin, Nurdin; Lisnawati, Sri Dewi; Marakarma, Andi; Yamani, Gasim (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the management of research collaboration between lecturers and students within the context of implementing the Independent Learning and Independent Campus (MBKM) framework. This research employs a qualitative case study approach, collecting data through direct observation, in-depth interviews, and analysis of institutional documents. The results show that the university has implemented an institutional policy that requires collaboration between lecturers and students in every university-funded research cluster. The number of students involved is adjusted according to the amount of research funding, with measurable publication targets ranging from the Sinta journal to reputable international journals indexed in Scopus. The university also provides 36 journals and two proceedings as a means of scientific dissemination, supporting a culture of publication from an early age. In addition, students are actively involved in community service-based research relevant to their scientific fields, creating a contextual learning experience that strengthens both academic skills and social contributions. The implications of this study suggest that a collaborative approach between lecturers and students in research can enhance the quality of academic publications and enhance students' research skills. Through university support in providing journals and proceedings, as well as student involvement in community service-based research, contextual and socially beneficial learning is created.